2018
DOI: 10.18203/2319-2003.ijbcp20185172
|View full text |Cite
|
Sign up to set email alerts
|

Relative oral bioavailability of three formulations of vitamin D3: An open-label, three-treatment study

Abstract: Background: Supplementation of vitamin D2 or vitamin D3 is recommended for vitamin D deficiency. Weekly supplementation of 60,000 IU of vitamin D3 increases serum 25(OH) D to optimal values. Various marketed forms of vitamin D3 include tablets, capsule, granules and oral solution. The main objective of this study is to compare the relative bioavailability of vitamin D3 oral solution with vitamin D3 tablet and capsule.Methods: This is an open-label, randomized, single-dose, three-treatment study to compare the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…In general, the availability for the absorption of a drug is more in oral solutions comparing to the capsule and tablet, respectively (12). In accordance to this, our previous bioequivalent study conducted in healthy volunteers, in which we had first time compared three different formulations (tablet, capsule, and oral solution) of vitamin D 3 and proved that the C max and AUC of an oral solution of vitamin D 3 are higher than that of the tablet and capsule (13). The aim of the present study is to compare and assess the efficacy of oral solution of vitamin D 3 with that of tablets and capsules in hypovitaminosis D patients.…”
Section: Increase In Serum 25(oh)d Was Observed In Vitamin D 3 Oralsupporting
confidence: 55%
See 1 more Smart Citation
“…In general, the availability for the absorption of a drug is more in oral solutions comparing to the capsule and tablet, respectively (12). In accordance to this, our previous bioequivalent study conducted in healthy volunteers, in which we had first time compared three different formulations (tablet, capsule, and oral solution) of vitamin D 3 and proved that the C max and AUC of an oral solution of vitamin D 3 are higher than that of the tablet and capsule (13). The aim of the present study is to compare and assess the efficacy of oral solution of vitamin D 3 with that of tablets and capsules in hypovitaminosis D patients.…”
Section: Increase In Serum 25(oh)d Was Observed In Vitamin D 3 Oralsupporting
confidence: 55%
“…Moreover, in our previous study, we have compared the bioequivalence of vitamin D 3 oral solution with that of conventional vitamin D 3 tablets and capsules. We observed that the oral solution of vitamin D has higher C max and AUC as compared to tablet and capsule (13).…”
Section: Resultsmentioning
confidence: 72%
“…The availability for absorption decreases in the order: solution >suspension >powder-filled capsule >compressed tablet >coated tablet. [17][18][19] The main issue addressed by this trial was to establish comparison of three different forms of vitamin D treatment in normalizing 25(OH)D 3 level. The results showed that there was significant increase in 25(OH)D 3 level in all three groups at 2 months.…”
Section: Discussionmentioning
confidence: 99%
“…In the liver, vitamin D2 and D3 are converted to a prohormonecalcidiol (25-hydroxyvitamin D). The measurement of 25-hydroxyvitamin D isthe best method to diagnose the vitamin D status of a person [2,4]. Vitamin D and its metabolites also have numerous clinical applications, including its effectiveness in rickets, hyperparathyroidism, pseudo hypothyroidism, renal osteodystrophy, osteoporosis(steroid-induced, postmenopausal, senile), anticonvulsant drug-induced osteomalacia, hepatic disorders, depression, cancer, obesity, heart disease, Parkinson's disease, influenza, bacterial vaginitis, and many others [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation of vitamin D3 can be through various oral products; however, the absorption varies based on the dosage form used. In addition, nanotechnology is an effective way to improve the absorption, and thus, improves the bioavailability of oral vitamin D3 [4]. Thus, we included a product made with nanotechnology, the chewable tablet, in our study.…”
Section: Introductionmentioning
confidence: 99%